Solid electrolyte composition, solid electrolyte layer or electrode composite material, and lithium ion battery

By adding a compound of specific structures to the solid electrolyte, its problem of low decentralization in non -polar organic solvents is solved, the coating and ion conductivity are improved, and the deterioration of solid electrolyte is suppressed.

CN119365937APending Publication Date: 2025-01-24IDEMITSU KOSAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047130.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-07-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The dispersion of the conventional solid electrolyte in non-polar organic solvents is low, resulting in insufficient coating properties, and the polar solvent may deteriorate the solid electrolyte.

Method used

By adding compounds with specific structures, such as compounds represented by formulas (1) to (3), to the solid electrolyte, its dispersibility in non-polar organic solvents is improved.

Benefits of technology

It achieves high dispersion in non-polar solvents, improves the coating properties of all-solid-state lithium-ion batteries, suppresses the degradation of solid electrolytes, and maintains high ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365937A_ABST
    Figure CN119365937A_ABST
Patent Text Reader

Abstract

A solid electrolyte composition comprising: (A) a sulfide solid electrolyte containing lithium, phosphorus, and sulfur; and (B) one or more compounds selected from among compounds represented by formulae (1)-(3). R < 11 > R < 12 > R < 13 > PO (1); (NR21R22) (NR23R24) (NR25R26) PO (2); (R31O) (R32O) (R33O) PO (3).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte composition, a solid electrolyte layer or an electrode composite material, and a lithium ion battery. Background Art

[0002] All-solid-state lithium-ion batteries are becoming more and more popular due to their high safety and other reasons, and various studies have been conducted to improve their performance (for example, Patent Document 1).

[0003] In the manufacture of all-solid lithium-ion batteries, solid electrolytes are sometimes applied in a slurry state, but conventional solid electrolytes have technical problems such as low dispersibility and insufficient coating properties in various organic solvents. In contrast, polar solvents such as butyl butyrate are sometimes used to improve dispersibility, but polar solvents may degrade solid electrolytes, so solid electrolytes with high dispersibility in non-polar solvents are particularly needed.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-166994 Summary of the invention

[0007] An object of the present invention is to provide a solid electrolyte composition having excellent dispersibility in a non-polar organic solvent.

[0008] The present inventors have conducted intensive studies and have found that the above-mentioned technical problems can be solved by adding a compound having a specific structure to a solid electrolyte, thereby completing the present invention.

[0009] According to the present invention, the following solid electrolyte composition and the like can be provided.

[0010] 1. A solid electrolyte composition comprising: (A) a sulfide solid electrolyte containing lithium, phosphorus and sulfur; and

[0011] (B) One or more compounds selected from the group consisting of compounds represented by the following formulae (1) to (3).

[0012] R 11 R 12 R 13 PO(1)

[0013] (NR 21 R 22 )(NR 23 R 24 )(NR 25 R 26 )PO(2)

[0014] (R 31O)(R 32 O)(R 33 O)PO(3)

[0015] (In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA.

[0016] In formula (2), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R is mutually bonded to form a substituted or unsubstituted saturated or unsaturated ring, or is not mutually bonded. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA.

[0017] In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB.

[0018] The substituent RA is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0019] The substituent RB is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0020] 2. The solid electrolyte composition according to 1, wherein in the formula (1) of the component (B), R 11 ~R 13 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms.

[0021] 3. The solid electrolyte composition according to 1 or 2, wherein in the formula (1) of the component (B), R 11 ~R 13Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms.

[0022] 4. The solid electrolyte composition according to any one of 1 to 3, wherein in the formula (2) of the component (B), R 21 ~R 26 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms.

[0023] 5. The solid electrolyte composition according to any one of 1 to 3, wherein in the formula (2) of the component (B), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of them is bonded to each other to form a substituted or unsubstituted saturated or unsaturated ring.

[0024] 6. The solid electrolyte composition according to any one of 1 to 5, wherein in the formula (3) of the component (B), R 31 ~R 33 Each independently represents a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms.

[0025] 7. The solid electrolyte composition according to any one of 1 to 6, wherein the compound represented by the formula (1) is used as the component (B), and further comprises a compound represented by the following formula (X1).

[0026] R X1 R X2 R X3 P(X1)

[0027] (In formula (X1), R X1 ~R X3 are independently a hydrogen atom or a substituent RA, R X1 ~R X3 At least one of them is a substituent RA. )

[0028] 8. The solid electrolyte composition according to any one of 1 to 7, wherein the ratio of the component (B) is 0.1 to 20% by mass relative to the total of the component (A) and the component (B).

[0029] 9. The solid electrolyte composition according to any one of 1 to 8, wherein the ratio of each of the components (B) exceeds 5% by volume with respect to the entire solid electrolyte composition.

[0030] 10. The solid electrolyte composition according to any one of 1 to 9, wherein the component (A) further contains a halogen atom.

[0031] 11. The solid electrolyte composition according to any one of 1 to 10, wherein the component (A) contains one or more elements selected from the group consisting of chlorine (Cl), bromine (Br), and iodine (I).

[0032] 12. The solid electrolyte composition according to any one of 1 to 11, wherein the component (A) contains chlorine (Cl).

[0033] 13. The solid electrolyte composition according to any one of 1 to 12, wherein the component (A) contains chlorine (Cl) and bromine (Br).

[0034] 14. The solid electrolyte composition according to any one of 1 to 13, wherein the component (A) has a crystalline structure.

[0035] 15. The solid electrolyte composition according to any one of 1 to 14, wherein the component (A) has an argyrodite-type crystal structure.

[0036] 16. The solid electrolyte composition according to any one of 1 to 14, wherein the component (A) has a sulfide crystalline lithium superion conductor region type II crystal structure.

[0037] 17. The solid electrolyte composition according to any one of 1 to 16, comprising (C) a solvent.

[0038] 18. The solid electrolyte composition according to any one of 1 to 16, which does not substantially contain (C) a solvent.

[0039] 19. The solid electrolyte composition according to any one of 1 to 18, comprising (D) an electrode active material.

[0040] 20. A solid electrolyte layer or an electrode composite material obtained from the solid electrolyte composition according to any one of 1 to 19.

[0041] 21. A lithium ion battery comprising the solid electrolyte layer or electrode composite material according to 20.

[0042] 22. A lithium ion battery, wherein at least one of its electrodes and solid electrolyte layers comprises: (A) a sulfide solid electrolyte containing lithium, phosphorus and sulfur; and (B) one or more compounds selected from the compounds represented by the following formulae (1) to (3).

[0043] R 11 R 12 R 13 PO(1)

[0044] (NR 21 R 22 )(NR 23 R 24 )(NR25 R 26 )PO(2)

[0045] (R 31 O)(R 32 O)(R 33 O)PO(3)

[0046] (In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA.

[0047] In formula (2), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R is mutually bonded to form a substituted or unsubstituted saturated or unsaturated ring, or is not mutually bonded. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA.

[0048] In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB.

[0049] The substituent RA is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0050] The substituent RB is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0051] According to the present invention, a solid electrolyte composition having excellent dispersibility in a nonpolar organic solvent can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The solid electrolyte composition of Comparative Example 1 was measured. 31PNMR spectrum, solid measured for component B1 (TOPO) 31 PNMR spectrum and solid electrolyte composition measured in Example 3 31 PNMR spectra arranged top and bottom.

[0053] Figure 2 The solid electrolyte composition of Example 3 is shown in FIG. 31 Plot of the contact time dependence of each peak of the PNMR spectrum.

[0054] Figure 3 The component B1 (TOPO) is measured 1 HNMR spectrum and the solid electrolyte composition of Example 3 measured 1 HNMR spectra arranged top to bottom.

[0055] Figure 4 The solid electrolyte composition of Example 3 is measured 6 LiNMR spectrum (single pulse method) and solid electrolyte composition measured for Example 3 6 LiNMR spectrum (CP / MAS method) arranged top to bottom. DETAILED DESCRIPTION

[0056] The solid electrolyte composition, solid electrolyte layer or electrode composite material, and lithium ion battery of the present invention are described below. In this specification, "x to y" represents a numerical range of "above x and below y". Regarding a technical matter, when there are multiple lower limits such as "above x", or when there are multiple upper limits such as "below y", it is possible to arbitrarily select and combine from the upper and lower limits.

[0057] 1. Solid electrolyte composition

[0058] A solid electrolyte composition according to one embodiment of the present invention contains the following component (A) and component (B).

[0059] (A) Sulfide solid electrolyte containing lithium, phosphorus and sulfur

[0060] (B) one or more compounds selected from the compounds represented by the following formulae (1) to (3)

[0061] R 11 R 12 R 13 PO(1)

[0062] (NR 21 R 22 )(NR 23 R 24 )(NR 25 R26 )PO(2)

[0063] (R 31 O)(R 32 O)(R 33 O)PO(3)

[0064] (In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA.

[0065] In formula (2), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R is mutually bonded to form a substituted or unsubstituted saturated or unsaturated ring, or is not mutually bonded. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA.

[0066] In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB.

[0067] The substituent RA is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0068] The substituent RB is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

[0069] The above-mentioned solid electrolyte composition includes component (B) in addition to the solid electrolyte, thereby exhibiting high dispersibility for various organic solvents, particularly excellent dispersibility for non-polar solvents such as toluene and xylene, and being able to maintain its dispersed state for a long time. As a result, it is expected that the coating property during the manufacture of the all-solid lithium ion battery will be improved, and it is also expected that the effect of exerting the battery performance will be greater while suppressing the degradation of the solid electrolyte.

[0070] The mechanism of the above effect is not yet clear, but it is believed that the particle surface of the solid electrolyte is modified by the modification of the component (B) having a specific structure, and the affinity with the non-polar organic solvent is improved, thereby achieving a uniform dispersion state of the solid electrolyte. Specifically, it is believed that the oxygen atom at the P=O site of the component (B) coordinates with the lithium atom on the surface of the component (A), and the other parts of the component (B), that is, the specific organic group bonded to the P atom, are arranged radially from the surface of the component (A), thereby improving the affinity of the component (A) with the non-polar solvent, and producing the above-mentioned effect. Here, the key point is to use the specific structure defined in formulas (1) to (3) as the other parts. If a structure other than this, such as an alkoxy group, is used, high dispersibility cannot be obtained. It is believed that the reason is that the oxygen atom in the alkoxy group is attracted by the lithium atom on the surface of the component (A), and the alkyl part is arranged along the surface of the component (A). Even when the other part contains an oxygen atom, as long as the structure is bulky like an aryloxy group, the aryl part is arranged to protrude from the surface of the component (A), and therefore the above-mentioned effect can be exerted without any problem.

[0071] In addition, when an organic material is added to a solid electrolyte, a decrease in ionic conductivity is inevitable compared to the case of using a solid electrolyte alone, but by using component (B), the decrease in ionic conductivity can be suppressed to a minimum, and high ionic conductivity can be maintained. It is believed that such an effect is also brought about by the action of component (B) having a specific structure.

[0072] Hereinafter, each structure of the solid electrolyte composition according to one embodiment of the present invention will be described.

[0073] (Component (A): solid electrolyte)

[0074] As the component (A), any solid electrolyte may be used without particular limitation as long as it is a sulfide solid electrolyte containing a specific element.

[0075] The sulfide solid electrolyte is a solid electrolyte that contains at least sulfur atoms and exhibits ion conductivity caused by the metal atoms contained therein. In addition to sulfur atoms, it preferably contains lithium atoms and phosphorus atoms, and more preferably contains lithium atoms, phosphorus atoms and halogen atoms, and is a solid electrolyte with ion conductivity caused by lithium atoms.

[0076] The sulfide solid electrolyte may be an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte.

[0077] (Amorphous sulfide solid electrolyte)

[0078] The amorphous sulfide solid electrolyte refers to an amorphous sulfide solid electrolyte whose X-ray diffraction pattern is a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the solid raw material.

[0079] As an amorphous sulfide solid electrolyte, any solid electrolyte that contains at least sulfur atoms and exhibits ionic conductivity caused by the metal atoms contained therein can be used without particular limitation. As representative solid electrolytes, for example, solid electrolytes containing sulfur atoms, lithium atoms and phosphorus atoms, such as Li2S-P2S5 (Li3PS4) composed of lithium sulfide and phosphorus sulfide; solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr; and solid electrolytes that also contain other elements such as oxygen and silicon, such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ion conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred.

[0080] The types of elements constituting the amorphous sulfide solid electrolyte can be identified by, for example, an ICP emission spectrometer.

[0081] When the amorphous sulfide solid electrolyte has at least Li2S-P2S5, from the viewpoint of obtaining higher ion conductivity, the molar ratio of Li2S to P2S5 is preferably 65-85:15-35, more preferably 70-80:20-30, and further preferably 72-78:22-28.

[0082] For example, when the amorphous sulfide solid electrolyte is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0083] When the amorphous sulfide solid electrolyte contains lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, the blending ratio (molar ratio) of these atoms is preferably 1.0 to 1.8: 1.0 to 2.0: 0.1 to 0.8: 0.01 to 0.6, more preferably 1.1 to 1.7: 1.2 to 1.8: 0.2 to 0.6: 0.05 to 0.5, and further preferably 1.2 to 1.6: 1.3 to 1.7: 0.25 to 0.5: 0.08 to 0.4.

[0084] In addition, when bromine and iodine are used in combination as halogen atoms, the blending ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine atoms and iodine atoms is preferably 1.0-1.8: 1.0-2.0: 0.1-0.8: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 1.2-1.8: 0.2-0.6: 0.02-0.25: 0.02-0.25, more preferably 1.2-1.6: 1.3-1.7: 0.25-0.5: 0.03-0.2: 0.03-0.2, and further preferably 1.35-1.45: 1.4-1.7: 0.3-0.45: 0.04-0.18: 0.04-0.18. By setting the mixing ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, a solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure described later and having higher ion conductivity can be easily obtained.

[0085] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.

[0086] In this specification, the average particle size (D 50 ) is the particle size when the particle size distribution cumulative curve is drawn starting from the smallest particle and the total particle size reaches 50%, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device.

[0087] (Crystalline sulfide solid electrolyte)

[0088] The crystalline sulfide solid electrolyte refers to a solid electrolyte in which a peak derived from the solid electrolyte is observed in the X-ray diffraction pattern in the X-ray diffraction measurement, and is a material that is independent of the presence or absence of a peak derived from the solid raw material. That is, the crystalline sulfide solid electrolyte contains a crystal structure derived from the solid electrolyte, and may be a part of the crystal structure derived from the solid electrolyte, or may be a whole of the crystal structure derived from the solid electrolyte. As long as the crystalline sulfide solid electrolyte has the above-mentioned X-ray diffraction pattern, it may also contain an amorphous solid electrolyte in part.

[0089] As the crystalline sulfide solid electrolyte, for example, so-called glass ceramics obtained by heating the above-mentioned amorphous sulfide solid electrolyte to a crystallization temperature or higher may be used. A sulfide solid electrolyte having the following crystal structure can be used.

[0090] Examples of the crystal structure that a crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, and phosphorus atoms may have include Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0091] In addition, examples of the crystal structure that the crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms may have include Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). Here, "thio-LISICON Region II type crystal structure" means Li 4- x Ge 1-x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x Any one of the crystal structures in the thio-LISICON Region II type similar crystal structure of S4 class lithium superionic conductor sulfide crystals.

[0092] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear near 2θ = 17.5°, 18.3°, 26.1°, 27.3°, 30.0°, for example. The diffraction peaks of the Li4P2S6 crystal structure appear near 2θ = 16.9°, 27.1°, 32.5°, for example. The diffraction peaks of the Li7PS6 crystal structure appear near 2θ = 15.3°, 25.2°, 29.6°, 31.0°, for example. The diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, 30.0°, for example. Li 4-x Ge 1-x P x The diffraction peaks of the thio-LISICON Region II type crystal structure of S4 class lithium superionic conductor sulfide crystals appear near 2θ = 20.1°, 23.9°, 29.5°, for example, similar to Li 4-x Ge 1-x P x The diffraction peaks of the thio-LISICON Region II type similar crystal structure of S4 class lithium superionic conductor sulfide crystals appear near 2θ = 20.2°, 23.6°, for example. In addition, regarding these peak positions, they can fluctuate within the range of ±0.5°.

[0093] In addition, as the crystal structure of the crystalline sulfide solid electrolyte, the argyrodite type crystal structure can also be cited. As the argyrodite type crystal structure, for example, the Li7PS6 crystal structure can be cited; the crystal structure represented by the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y S6 (where x is from -0.6 to 0.6 and y is from 0.1 to 0.6); the crystal structure represented by Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5); the crystal structure represented by Li 7-x PS 6-x Hax (Ha is Cl or Br, and x is preferably 0.2 to 1.8)

[0094] Among the above-mentioned crystal structures, the preferred crystal structures as the crystal structures possessed by the crystalline sulfide solid electrolyte are the Li3PS4 crystal structure, the sulfide crystalline lithium superion conductor region type II crystal structure, and the argyrodite type crystal structure.

[0095] The shape of the crystalline sulfide solid electrolyte is not particularly limited, but a particle shape can be mentioned, for example. The average particle size (D 50 ) and the average particle size (D 50 ) Similarly, for example, it can be exemplified within the range of 0.01 μm to 500 μm and 0.1 to 200 μm.

[0096] (Component (B): Compounds represented by formula (1) to (3))

[0097] As component (B), one or more compounds selected from the compounds represented by formula (1) to (3) are used. One of them may be used alone, or two or more of them may be used in combination. In addition, impurities generated in the manufacturing process of component (B) that cannot be substantially removed or purified may also be included.

[0098] In one embodiment, the molecular weight of component (B) is 1 to 10,000, 1 to 5,000, 1 to 3,000, or 1 to 1,000.

[0099] Hereinafter, each component (B) will be described.

[0100] In addition, the substituent RA in formula (1) and (2) is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms. When a plurality of RA are present in one compound, the plurality of RA may be the same or different.

[0101] The substituent RB in formula (3) is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms. When a plurality of RBs exist in one compound, the plurality of RBs may be the same or different.

[0102] As the substituent in the case of "substituted or unsubstituted", there may be mentioned an alkyl group having 1 to 50 carbon atoms, an alkenyl group having 2 to 50 carbon atoms, an alkynyl group having 2 to 50 carbon atoms, a cycloalkyl group having 3 to 50 ring carbon atoms, an aryl group having 6 to 50 ring carbon atoms, or a monovalent heterocyclic group having 5 to 50 ring atoms.

[0103] In one embodiment, the substituent RA is an unsubstituted group.

[0104] In one embodiment, the substituent RB is an unsubstituted group.

[0105] (Compound represented by formula (1))

[0106] R 11 R 12 R 13 PO(1)

[0107] In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA.

[0108] In one embodiment, R 11 ~R 13 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms. The carbon atoms may be, for example, 1 to 30, 1 to 20, or 1 to 15.

[0109] In one embodiment, R 11 ~R 13 are each independently a substituted or unsubstituted alkyl group having 4 to 20 carbon atoms. In this case, R 11 ~R 13 The total carbon number of may be 12-60, 12-50, or 12-40.

[0110] In one embodiment, R 11 ~R 13 Each independently represents a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms. The carbon atoms may be, for example, 6 to 20, 6 to 15, or 6 to 10.

[0111] (Compound represented by formula (2))

[0112] (NR 21 R 22 )(NR 23 R 24 )(NR 25 R 26 )PO(2)

[0113] In formula (2), R 21With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R is mutually bonded to form a substituted or unsubstituted saturated or unsaturated ring, or is not mutually bonded. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA.

[0114] In formula (2), R 21 With R 22 When they are bonded to each other to form a substituted or unsubstituted saturated or unsaturated ring, the formed ring may be, for example, a nitrogen-containing ring structure having 3 to 10 carbon atoms, for example, a structure containing a pyrrolidine skeleton. 23 With R 24 , and R 25 With R 26 It can also be done by and R 21 With R 22 The ring is formed in the same way.

[0115] In one embodiment, R 21 ~R 26 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms. The carbon atoms may be, for example, 1 to 30, 1 to 20, or 1 to 15.

[0116] (Compound represented by formula (3))

[0117] (R 31 O)(R 32 O)(R 33 O)PO(3)

[0118] In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB.

[0119] In one embodiment, R 31 ~R 33 Each independently represents a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms. The carbon atoms may be, for example, 6 to 20, 6 to 15, or 6 to 10.

[0120] As described above, the compounds represented by formula (1) to (3) all contribute greatly to the effect of the present invention. However, in one embodiment, as component (B), a compound represented by formula (1) or formula (3) is used. In this case, in addition to high dispersibility in organic solvents, an effect of maintaining ion conductivity at a high level can also be obtained. In particular, in formula (1), R 11 ~R 13 are each independently a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, and in the formula (3), R 31 ~R 33 When each of the groups is independently a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, this effect is more significant.

[0121] (Solid Electrolyte Composition)

[0122] The solid electrolyte composition according to one embodiment of the present invention is not particularly limited as long as it contains the component (A) and the component (B).

[0123] In one embodiment, the ratio of component (B) (the total amount when containing a plurality of components (B)) is 0.1 to 20 mass % relative to the total of component (A) and component (B), and may be 1 to 20 mass %, 2 to 15 mass %, or 3 to 10 mass %.

[0124] In one embodiment, the proportion of each component (B) is more than 5 volume %, 10 volume % or more, 15 volume % or more, or 20 volume % or more relative to the entire solid electrolyte composition.

[0125] In one embodiment, the ion conductivity of the solid electrolyte composition is 1.40 mS / cm or more, for example, 1.50 mS / cm or more, 2.00 mS / cm or more, 3.00 mS / cm or more, 4.00 mS / cm or more, or 5.00 mS / cm or more.

[0126] The ionic conductivity was measured by the method described in Examples.

[0127] In one embodiment, in addition to the component (B), a compound represented by the following formula (X1) (hereinafter, sometimes referred to as the component (Bα)) may be contained.

[0128] R X1 R X2 R X3 P(X1)

[0129] In formula (X1), R X1 ~R X3 are independently a hydrogen atom or a substituent RA, R X1 ~R X3At least one of them is a substituent RA. The substituent RA is as described above.

[0130] In one embodiment, R X1 ~R X3 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms. The carbon atoms may be, for example, 1 to 30, 1 to 20, or 1 to 15.

[0131] In one embodiment, R X1 ~R X3 are each independently a substituted or unsubstituted alkyl group having 4 to 20 carbon atoms. In this case, R 11 ~R 13 The total carbon number of may be 12-60, 12-50, or 12-40.

[0132] In one embodiment, a compound represented by formula (1) is used as the component (B), and further a component (Bα) is used.

[0133] The mass ratio of the component (B) to the component (Bα) is, for example, 1:9 to 9:1 or 2:8 to 8:2.

[0134] The solid electrolyte composition of one embodiment of the present invention may contain (C) solvent, or may not contain (C) solvent substantially, or may not contain (C) solvent. Substantially not containing refers to, for example, a small amount of solvent that cannot be completely removed even if a solvent removal operation is performed. As a solvent, a known solvent can be used.

[0135] The solid electrolyte composition according to one embodiment of the present invention may contain (D) an electrode active material. The electrode active material will be described below.

[0136] In one embodiment, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass of the solid electrolyte composition is:

[0137] Components (A) and (B);

[0138] Components (A), (B) and component (Bα);

[0139] Components (A), (B) and (C);

[0140] Components (A), (B), component (Bα) and (C);

[0141] Components (A), (B) and (D);

[0142] Components (A), (B), component (Bα) and (D);

[0143] Components (A), (B), (C) and (D); or

[0144] Components (A), (B), component (Bα), (C) and (D).

[0145] In one embodiment, the proportion of compounds having a molecular weight of 10,000 or less in all components other than component (A) in the solid electrolyte composition is 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass.

[0146] In one embodiment, the proportion of the compound having a molecular weight exceeding 10,000 in the solid electrolyte composition is 20% by mass or less, 10% by mass or less, 5% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.1% by mass or less, or 0% by mass.

[0147] The molecular weight of the high molecular weight component is a number average molecular weight (Mn) measured by GPC (Gel Permeation Chromatograpy).

[0148] 2. Solid electrolyte layer or electrode composite material

[0149] The solid electrolyte composition according to one embodiment of the present invention can be used for a solid electrolyte layer, a positive electrode, a negative electrode, and the like of a lithium ion secondary battery or the like.

[0150] (Solid electrolyte layer)

[0151] A solid electrolyte layer according to one embodiment of the present invention includes the above-mentioned solid electrolyte composition, or is produced from the above-mentioned solid electrolyte composition.

[0152] The solid electrolyte layer may contain only the above-mentioned solid electrolyte composition, or may be made only from the above-mentioned solid electrolyte composition, and may further contain a binder. As the binder, the same binder as that described in the negative electrode composite material described later can be used.

[0153] The other structures of the above-mentioned solid electrolyte layer are as described in the solid electrolyte layer of the lithium ion battery described later.

[0154] (Electrode Composite Materials)

[0155] The electrode composite material of one embodiment of the present invention comprises the above-mentioned solid electrolyte composition and an active material, or is manufactured from a composition comprising the above-mentioned solid electrolyte composition and an active material. If a negative electrode active material is used as the active material, it becomes a negative electrode composite material, and if a positive electrode active material is used as the active material, it becomes a positive electrode composite material.

[0156] (Negative electrode composite material)

[0157] As the negative electrode active material used in the negative electrode composite material, for example, carbon materials and metal materials can be used. A composite composed of two or more of them can also be used. In addition, negative electrode active materials developed in the future can also be used. In addition, it is preferred that the negative electrode active material has electronic conductivity.

[0158] Examples of carbon materials include graphite (e.g., artificial graphite), graphite carbon fiber, resin-fired carbon, pyrolysis vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-fired carbon, polyphenylene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon.

[0159] As the metal material, a metal single substance, an alloy, and a metal compound may be mentioned. As the metal single substance, metal silicon, metal tin, metal lithium, metal indium, and metal aluminum may be mentioned. As the alloy, an alloy containing at least one of silicon, tin, lithium, indium, and aluminum may be mentioned. As the metal compound, a metal oxide may be mentioned. Metal oxides are, for example, silicon oxide, tin oxide, and aluminum oxide.

[0160] In one embodiment, the mixing ratio of the negative electrode active material and the solid electrolyte composition is negative electrode active material: solid electrolyte composition (mass ratio) = 95:5 to 5:95, 90:10 to 10:90, or 85:15 to 15:85.

[0161] The negative electrode composite material may further include a conductive aid. When the electron conductivity of the negative electrode active material is low, it is preferred to add a conductive aid. The conductive aid only needs to have conductivity, and its electron conductivity is preferably 1×10 3 S / cm or more, more preferably 1×10 5 S / cm or more.

[0162] Specific examples of the conductive aid include preferably a substance containing at least one element selected from the group consisting of carbon materials, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten and zinc, and more preferably a carbon single substance with high conductivity or a carbon material other than a carbon single substance; a metal single substance, a mixture or a compound containing nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium or rhodium.

[0163] In addition, specific examples of carbon materials include carbon black such as Ketjen black, acetylene black, DENKA BLACK, thermal black, channel black, etc.; graphite, carbon fiber, activated carbon, etc., which can be used alone or in combination of two or more. Among them, acetylene black, DENKA BLACK, and Ketjen black having high electron conductivity are preferred.

[0164] When the negative electrode composite material contains a conductive auxiliary agent, the content of the conductive auxiliary agent in the composite material is preferably 1 to 40% by mass, and more preferably 2 to 20% by mass.

[0165] In order to closely bind the negative electrode active material and the solid electrolyte composition to each other, a binder may be further contained.

[0166] As the binder, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), fluorine rubber, or thermoplastic resins such as polypropylene and polyethylene, ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, natural butyl rubber (NBR), etc. can be used alone or as a mixture of two or more. In addition, cellulose as a water-based binder, an aqueous dispersion of styrene-butadiene rubber (SBR), etc. can also be used.

[0167] The negative electrode composite material can be produced by mixing a solid electrolyte composition and a negative electrode active material, or a solid electrolyte composition, a negative electrode active material, and any conductive additive and / or binder.

[0168] The mixing method is not particularly limited, and for example, dry mixing using a mortar, ball mill, bead mill, jet mill, planetary ball mill, vibrating ball mill, sand mill, or chopper mill can be applied; and wet mixing using a mortar, ball mill, bead mill, planetary ball mill, vibrating ball mill, sand mill, or FILMIX after the raw materials are dispersed in an organic solvent, and then the solvent is removed. Among them, wet mixing is preferred in order not to destroy the negative electrode active material particles.

[0169] (Positive electrode composite material)

[0170] The positive electrode active material used in the positive electrode composite material is a material capable of inserting and extracting lithium ions, and a material known as a positive electrode active material in the battery field can be used. In addition, a positive electrode active material to be developed in the future can also be used.

[0171] Examples of the positive electrode active material include metal oxides and sulfides. Sulfides include metal sulfides and non-metal sulfides.

[0172] The metal oxide is, for example, a transition metal oxide. Specifically, V2O5, V6O 13 , LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(Ni a Co b Mn c )O2(here, 0 <a<1,0<b<1,0<c<1,a+b+c=1)、LiNi 1-Y Co Y O2、LiCo1-Y Mn Y O2, LiNi 1-Y Mn Y O2 (where 0 ≤ Y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O4, LiMn 2-Z Co Z O4 (where 0 < Z < 2), LiCoPO4, LiFePO4, CuO, Li(Ni a Co b Al c )O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), etc.

[0173] As metal sulfides, titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), nickel sulfide (Ni3S2), etc. can be cited. In addition, as metal oxides, bismuth oxide (Bi2O3), bismuth lead oxide (Bi2Pb2O5), etc. can be cited.

[0174] As non-metal sulfides, organic disulfide compounds, carbon sulfide compounds, etc. can be cited.

[0175] In addition to the above, niobium selenide (NbSe3), indium metal, and sulfur can also be used as the positive electrode active material.

[0176] The positive electrode composite material can further contain a conductive additive. The conductive additive is the same as the conductive additive described in the negative electrode composite material.

[0177] The blending ratio of the solid electrolyte composition in the positive electrode composite material to the positive electrode active material is the same as the blending ratio of the solid electrolyte composition to the negative electrode active material described above. The content of the conductive additive in the positive electrode composite material is the same as the content of the conductive additive in the negative electrode composite material described above. The manufacturing method of the positive electrode composite material is the same as the manufacturing method of the negative electrode composite material described above.

[0178] 3. Lithium-ion battery

[0179] One embodiment of the lithium-ion battery (the first lithium-ion battery) of the present invention includes one or more selected from the group consisting of the above solid electrolyte layer, negative electrode composite material, and positive electrode composite material, or includes one or more selected from the group consisting of the above solid electrolyte layer, negative electrode layer manufactured from the above negative electrode composite material, and positive electrode layer manufactured from the above positive electrode composite material.

[0180] A lithium-ion battery generally has a structure in which a negative electrode layer, an electrolyte layer, and a positive electrode layer are stacked in this order.

[0181] (Negative electrode layer)

[0182] When the negative electrode composite material of one embodiment of the present invention is used as the negative electrode layer, the negative electrode composite material is as described above. When a material other than the negative electrode composite material of one embodiment of the present invention is used as the negative electrode layer, a known structure may be used.

[0183] The thickness of the negative electrode layer is, for example, 100 nm to 5 mm, 1 μm to 3 mm, or 5 μm to 1 mm.

[0184] The negative electrode layer can be produced by a known method, for example, a coating method or an electrostatic method (e.g., an electrostatic spray method or an electrostatic screen method).

[0185] (Electrolyte layer)

[0186] When the solid electrolyte layer of one embodiment of the present invention is used as the electrolyte layer, the solid electrolyte layer is as described above. When a layer other than the solid electrolyte layer of one embodiment of the present invention is used as the electrolyte layer, a known structure may be adopted.

[0187] The thickness of the electrolyte layer is, for example, not less than 0.001 mm and not more than 1 mm.

[0188] The solid electrolyte of the electrolyte layer may be welded. Welding means that a part of the solid electrolyte particles melts and the melted part is integrated with other solid electrolyte particles. In addition, the electrolyte layer may also be a plate-like body of a solid electrolyte. As the plate-like body, it also includes the case where a part or all of the solid electrolyte particles melt to form a plate-like body.

[0189] The electrolyte layer can be produced by a known method, for example, a coating method or an electrostatic method (e.g., an electrostatic spray method, an electrostatic screen method, etc.).

[0190] (Positive electrode layer)

[0191] When the positive electrode composite material of one embodiment of the present invention is used as the positive electrode layer, the positive electrode composite material is as described above. When a material other than the positive electrode composite material of one embodiment of the present invention is used as the positive electrode layer, a known structure may be used.

[0192] The thickness of the positive electrode layer is, for example, not less than 0.01 mm and not more than 10 mm.

[0193] The positive electrode layer can be produced by a known method, for example, a coating method or an electrostatic method (e.g., an electrostatic spray method or an electrostatic screen method).

[0194] (Current Collector)

[0195] In one embodiment, the lithium ion battery includes a current collector. For example, the negative electrode current collector is provided on the negative electrode layer side opposite to the electrolyte layer side, and the positive electrode current collector is provided on the positive electrode layer side opposite to the electrolyte layer side.

[0196] As the current collector, a plate-like body, a foil-like body, or the like made of copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, indium, lithium, or an alloy thereof, or the like can be used.

[0197] The lithium-ion battery described above can be manufactured by laminating and joining the above-mentioned components. As a joining method, there are a method of stacking the components and applying pressure and crimping; a method of applying pressure between two rollers (roll to roll), etc. It is also possible to join the joining surface via an active material having ion conductivity and an adhesive material that does not hinder ion conductivity. During the joining process, heating and welding can be performed within a range where the crystal structure of the solid electrolyte does not change.

[0198] The above-mentioned lithium ion battery can also be manufactured by sequentially forming the above-mentioned components. It can be manufactured by a known method, for example, by a coating method or an electrostatic method (electrostatic spray method, electrostatic screen method, etc.).

[0199] In the lithium ion battery (second lithium ion battery) according to another embodiment of the present invention, at least one of the electrode (negative electrode layer and positive electrode layer) and the solid electrolyte layer contains the following component (A) and component (B).

[0200] (A) Sulfide solid electrolyte containing lithium, phosphorus and sulfur

[0201] (B) one or more compounds selected from the compounds represented by formula (1) to (3)

[0202] The component (A) and the component (B) are as described in the solid electrolyte composition according to one embodiment of the present invention.

[0203] As the second lithium ion battery, except that the provision in the first lithium ion battery that "comprising one or more selected from the group consisting of the above-mentioned solid electrolyte layer, the negative electrode composite material and the positive electrode composite material, or comprising one or more selected from the group consisting of the above-mentioned solid electrolyte layer, the negative electrode layer manufactured from the above-mentioned negative electrode composite material and the positive electrode layer manufactured from the above-mentioned positive electrode composite material" is changed to "at least one of the electrode and the solid electrolyte layer comprises the following components (A) and (B)", it is the same as the first lithium ion battery and each structure can be appropriately applied.

[0204] When each layer of the second lithium ion battery contains the component (A) and the component (B), the content ratio of the component (A) to the component (B) is as described in the solid electrolyte composition of one embodiment of the present invention.

[0205] Example

[0206] Hereinafter, the present invention will be described in more detail by way of examples.

[0207] The component (B) used in the following examples and the component (B') used in the comparative examples (components corresponding to the component (B)) are as follows. The alphabetical symbols described together are abbreviations of the respective compounds.

[0208] B1: Tri-n-octylphosphine oxide (TOPO)

[0209] B2: Triphenylphosphine oxide (TPPO)

[0210] B3: Tripyrrolidine phosphine oxide (TpydPO)

[0211] B4: Tris(diethylamino)phosphine oxide (HMPA)

[0212] B5: Triphenyl phosphate (PhPho)

[0213] B'1: Triethyl phosphate (TEPho)

[0214] [Chemistry 1]

[0215]

[0216] The evaluation methods in Examples and Comparative Examples are as follows.

[0217] (1) Ionic conductivity measurement

[0218] A sample of a solid electrolyte or a solid electrolyte composition is filled into a tablet forming machine, and a pressure of 400 MPa is applied to form a formed body (also called "granules", with a diameter of about 10 mm and a thickness of about 0.1 to 0.2 cm). Carbon is placed on both sides of the formed body as an electrode, and pressure is applied again using a tablet forming machine to produce a formed body for measurement. For the formed body for measurement, the ion conductivity is measured by AC impedance measurement. The value of the conductivity adopts the value at 25°C.

[0219] (2) Ionic conductivity maintenance rate

[0220] The degree of change in ionic conductivity caused by the addition of component (B) was measured. Specifically, in Examples 1 to 12 and Comparative Example 2, the rate of change in ionic conductivity was calculated based on the ionic conductivity in Comparative Example 1 using only the same component (A). In Example 13, the rate of change in ionic conductivity was calculated based on the ionic conductivity in Comparative Example 3 using only the same component (A).

[0221] (3) Dispersibility (transmittance evaluation)

[0222] The transmittance of a pulsed light source with a wavelength of 850 nm was measured using the "TURBISCAN CLASSIC (MA2000)" manufactured by Formulaction, thereby evaluating the dispersibility of the solid electrolyte composition. Specifically, 0.015 g of the solid electrolyte composition and 6 ml of p-xylene were mixed in a transparent spiral tube (8 ml), stirred for 10 seconds using an ultrasonic device, and a mixed solution was prepared. The mixed solution was transferred entirely to a special glass pool with a lid, and the above-mentioned MA2000 was used to measure for 30 minutes at 1 minute intervals to observe the changes over time (the height from the bottom of the glass pool to the liquid surface was about 6 cm). The liquid surface and the vicinity of the bottom surface are greatly affected by interference factors such as adhesion to the glass pool and convection caused by sample sedimentation, so it is difficult to evaluate samples with very different dispersivities using unified measurement conditions and analysis conditions. Therefore, the average transmittance at a position 30 to 35 mm from the bottom of the glass pool 15 minutes from the start of the measurement was used as a value representing the dispersibility of the entire sample, thereby performing a unified evaluation. If the dispersibility is high, the pulse light source will be scattered by the solid electrolyte composition, so the transmittance will decrease. If the dispersibility is low, the solid electrolyte composition will settle, so the pulse light source will pass through the glass cell and the transmittance will increase. At this time, the transmittance of the internal standard of the device is set to 100%.

[0223] Production Example 1 (Component (A): Production of Argentite-type Solid Electrolyte (Sulfide Solid Electrolyte))

[0224] (A) Preparation of raw material mixture

[0225] In a glove box of nitrogen atmosphere, the pulverized compounds were weighed so that the molar ratio was Li2S:P2S5:LiBr:LiCl=47.5:12.5:15.0:25.0, and the resulting substance was put into a glass container, and the container was shaken for rough mixing.

[0226] The raw materials obtained by rough mixing were dispersed in a mixed solvent of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and dehydrated isobutyronitrile (manufactured by Kishida Chemical Co., Ltd.) under a nitrogen atmosphere to prepare a raw material mixture slurry of about 10% by mass. The raw material mixture slurry was kept in a nitrogen atmosphere and mixed and crushed using a bead mill (LMZ015, manufactured by Ashizawa Finetech Co., Ltd.). The treated slurry was added to a Schlenk bottle replaced with nitrogen and dried under reduced pressure to prepare a raw material mixture.

[0227] (B) Firing process

[0228] The raw material mixture obtained in (A) above was heated in an electric furnace (F-1404-A, manufactured by Tokyo Glass Instrument Co., Ltd.) in a glove box under a nitrogen atmosphere. Specifically, the raw material mixture was placed in a sagger made of Al2O3 (999-60S, manufactured by Tokyo Glass Instrument Co., Ltd.) and heated at 430°C for more than 1 hour in an electric furnace. Then, the sagger was taken out of the electric furnace and slowly cooled to obtain an argyrodite-type solid electrolyte.

[0229] (C) Micro-particle forming process

[0230] The obtained argyrodite-type solid electrolyte was dispersed in a mixed solvent of dehydrated toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and dehydrated isobutyronitrile (manufactured by Kishida Chemical Co., Ltd.) under a nitrogen atmosphere to prepare a solid electrolyte slurry. While the slurry was kept in a nitrogen atmosphere, it was mixed and crushed using a bead mill (LMZ015, manufactured by Ashizawa Finetech Co., Ltd.). The treated solid electrolyte slurry was placed in a Schlenk bottle replaced with nitrogen, and then dried under reduced pressure to obtain a micronized argyrodite-type solid electrolyte (component (A): hereinafter also referred to as "A1").

[0231] As a result of X-ray diffraction (XRD) measurement, in the XRD pattern, peaks derived from an argyrodite type crystal structure were observed at 2θ=25.5±1.0 degrees and 29.9±1.0 degrees.

[0232] Production Example 2 (Component (A): Production of a solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure (sulfide solid electrolyte))

[0233] In a Schlenk bottle (capacity: 100 mL) equipped with a stirrer, 0.59 g of lithium sulfide, 0.95 g of phosphorus pentasulfide, 0.19 g of lithium bromide, and 0.28 g of lithium iodide were introduced under a nitrogen atmosphere. After the stirrer was rotated, 20 mL of tetramethylethylenediamine (TMEDA) as a complexing agent was added, and stirring was continued for 12 hours. The obtained complex-containing material was dried under vacuum (room temperature: 23°C) to obtain a powdered complex. Next, the powder of the complex was heated at 120°C under vacuum for 2 hours to obtain an amorphous sulfide solid electrolyte. Furthermore, the amorphous sulfide solid electrolyte was heated at 140°C under vacuum for 2 hours to obtain a crystalline sulfide solid electrolyte A2.

[0234] Example 1 (Preparation and Evaluation of Solid Electrolyte Composition)

[0235] Under a nitrogen atmosphere, in a 50mL Schlenk tube equipped with a stirrer, A1 and B1 (TOPO) were added in an amount of 1.5g in total in an amount of B1 relative to the total amount of A1 and B1, and 15.5mL toluene was added to make a mixture (slurry). Stirring was carried out at 60°C for 1 hour while maintaining a nitrogen atmosphere. Then, it was vacuum dried to a substantially dry powder state at room temperature, and vacuum dried at 80°C for 1 hour to obtain a solid electrolyte composition of a powder. The evaluation results of the obtained solid electrolyte composition are shown in Table 1.

[0236] In addition, the volume ratio (volume %) of B1 to the total volume of A1 and B1 is also shown in Table 1 (the same applies to the following Examples and Comparative Examples).

[0237] Embodiment 2, 3

[0238] The solid electrolyte composition was produced and evaluated by the same method as in Example 1 except that the amount of A1 and B1 was 3 mass % or 10 mass % relative to the total amount of A1 and B1.

[0239] Embodiments 4 to 6

[0240] A solid electrolyte composition was prepared and evaluated by the same method as in Example 1 except that B1 (TOPO) was used as component (B) and tri-n-octylphosphine (TOP) was further added. The results are shown in Table 1. The amounts of B1 (TOPO) and TOP were set to 0.5 mass %, 1.5 mass % or 5 mass % respectively in terms of the ratio relative to the total amount of A1, B1 and TOP.

[0241] Example 7

[0242] A solid electrolyte composition was prepared and evaluated by the same method as in Example 1 except that the amount of B1 was 3% by mass relative to the total amount of A1, B1 and TOP and the amount of TOP was 7% by mass relative to the total amount of A1, B1 and TOP. The results are shown in Table 1.

[0243] Embodiments 8 to 12

[0244] A solid electrolyte composition was prepared and evaluated by the same method as in Example 1 except that component (B) shown in Table 1 was used instead of B1 and the amount of component (B) relative to the total amount of A1 and component (B) was set to the amount shown in Table 1. The results are shown in Table 1.

[0245] Embodiment 13

[0246] A solid electrolyte composition was produced and evaluated in the same manner as in Example 1 except that A2 was used instead of A1 and the amount of B1 (TOPO) was 9 mass % relative to the total amount of A2 and B1. The results are shown in Table 1.

[0247] Comparative Example 1

[0248] The solid electrolyte composition was produced and evaluated in the same manner as in Example 1 except that the component (B) was not used. The results are shown in Table 1.

[0249] Comparative Example 2

[0250] A solid electrolyte composition was prepared and evaluated by the same method as in Example 1 except that the component (B') shown in Table 1 was used instead of B1 and the amount of the component (B') was set to the amount shown in Table 1 relative to the total amount of A1 and the component (B'). The results are shown in Table 1.

[0251] Comparative Example 3

[0252] The solid electrolyte composition was produced and evaluated in the same manner as in Example 13 except that the component (B) was not used. The results are shown in Table 1.

[0253] [Table 1]

[0254]

[0255] (1) In the dispersibility evaluation, the solid electrolyte compositions of Examples 1 to 12 had a transmittance of 0% even after 15 minutes from the start of stirring, and a uniform dispersion state could be maintained for a long time, confirming extremely high dispersibility. In Comparative Example 1 in which component (B) was not used, sedimentation of component (A) occurred 15 minutes after stirring, making it difficult to maintain the dispersion state. In addition, the dispersibility in Comparative Example 2 in which only component (B') other than component (B) was used was also the same as that in Comparative Example 1. It is believed that this is because the particle surface of component (A) (solid electrolyte) is modified by using component (B) having a specific structure, and the affinity of component (A) with the organic solvent is improved. In the comparison between Example 13 and Comparative Example 3 in which A2 is used as component (A), the relative superiority of the dispersibility in Example 13 is also confirmed.

[0256] (2) The solid electrolyte composition of Comparative Example 1 was measured. 31 PNMR spectrum (single pulse method), solid measured for component B1 (TOPO) 31 PNMR spectrum (Cross-Polarization / Magic-Angle Spinning method: Cross-Polarization / Magic Angle Spinning method, hereinafter referred to as "CP / MAS method") and solid electrolyte composition measured in Example 3 31 The PNMR spectrum (CP / MAS method) is shown in Figure 1 .Depend on Figure 1 It can be seen that a new peak is confirmed near 65 ppm in Example 3 compared with Comparative Example 1, and the peak is shifted to the low magnetic field side compared with the peak obtained when the component B1 (TOPO) is measured alone. This shows that in Example 3, by mixing B1 (TOPO) with the solid electrolyte, the electronic state around the P atom of B1 (TOPO) changes.

[0257] (3) The solid electrolyte composition of Example 3 was measured. 31 The contact time dependence of each peak in the PNMR spectrum (CP / MAS method) is shown in Figure 2 . The peak of component B1 (TOPO) temporarily increases and then tends to decay. It is believed that this is because the intensity increases due to the magnetization transfer from the hydrogen atoms contained in the alkyl group of component B1 (TOPO) to the P atoms, and then decays due to the spin-lattice relaxation behavior of 1H in the rotation system. On the other hand, the peak of the solid electrolyte increases monotonically with the increase of contact time. This shows that the arrangement of each atom is in the order of the alkyl group of component B1 (TOPO), the P atom of component B1 (TOPO), and the P atom of the solid electrolyte.

[0258] (4) The measured value of component B1 (TOPO) 1H MAS NMR spectrum and measured solid electrolyte composition of Example 3 1 The H MAS NMR spectrum is shown in Figure 3 . In the spectrum of Example 3, it can be seen that the ratio of the broad peak is reduced compared to the spectrum of component B1 (TOPO) alone. This shows that the molecular mobility is increased. The reason is not yet clear, but it can be considered that in the state where component B1 (TOPO) is arranged on the surface of the solid electrolyte, the alkyl groups of component B1 (TOPO) have a higher degree of freedom of movement with each other, and the molecular mobility is improved compared to the solid state of component B1 (TOPO) alone.

[0259] (5) The solid electrolyte composition of Example 3 was measured. 6 LiNMR spectrum (single pulse method) and solid electrolyte composition measured for Example 3 6 LiNMR spectrum (CP / MAS method) is shown in Figure 4 . In Example 3, a new peak was observed on the high magnetic field side of the Li atom contained in the solid electrolyte. If considered together with the peak change of the P atom described in (2), it can be considered that a new structure such as P=O··Li is generated (a structure in which the oxygen atom at the P=O site of component (B) is coordinated to the lithium atom on the surface of component (A)). If the results of (2) to (5) are considered comprehensively, as described at the beginning of the specification of this application, it can be considered that a structure in which at least a part of the site other than the oxygen atom of P=O in component (B) (i.e., a specific organic group bonded to the P atom) is radially arranged from the surface of component (A) is generated.

[0260] (6) If component (B) is used as an organic material, a decrease in ionic conductivity is inevitable compared to the case of using component (A) alone, but in Examples 1 to 13 using component (B) of a specific structure, the decrease is suppressed to a small extent, and it can be seen that high ionic conductivity is maintained. Among them, the ionic conductivity maintenance rates based on B1 (TOPO) and B5 (PhPho) are particularly high, and it can be seen that the two effects of improved dispersibility and maintenance of ionic conductivity can be exerted at a high level. On the other hand, it can be seen that in Comparative Example 2 using triethyl phosphate (TEPho), the ionic conductivity is reduced to 1.38 mS / cm, and the reduction in ionic conductivity caused by triethyl phosphate (TEPho) is relatively large.

[0261] The above embodiments and / or examples of the present invention have been described in some detail, but those skilled in the art can easily make many changes to these illustrative embodiments and / or examples without departing from the new teachings and effects of the present invention. Therefore, these many changes are included in the scope of the present invention.

[0262] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are hereby cited.

Claims

1. A solid electrolyte composition, characterized in that Include: (A) a sulfide solid electrolyte containing lithium, phosphorus and sulfur; and (B) one or more compounds selected from the group consisting of compounds represented by the following formulae (1) to (3), R 11 R 12 R 13 PO(1) (NR 21 R 22 )(NR 23 R 24 )(NR 25 R 26 )PO(2) (R 31 O)(R 32 O)(R 33 O)PO(3) In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA, In formula (2), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R in the formula (R) is bonded to each other to form a substituted or unsubstituted saturated or unsaturated ring, or is not bonded to each other. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA, In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB, The substituent RA is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms. The substituent RB is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

2. The solid electrolyte composition according to claim 1, characterized in that In the formula (1) of the component (B), R 11 ~R 13 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms.

3. The solid electrolyte composition according to claim 1 or 2, characterized in that In the formula (1) of the component (B), R 11 ~R 13 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms.

4. The solid electrolyte composition according to any one of claims 1 to 3, characterized in that In the formula (2) of the component (B), R 21 ~R 26 Each independently represents a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms.

5. The solid electrolyte composition according to any one of claims 1 to 3, characterized in that In the formula (2) of the component (B), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of them is bonded to each other to form a substituted or unsubstituted saturated or unsaturated ring.

6. The solid electrolyte composition according to any one of claims 1 to 5, characterized in that In the formula (3) of the component (B), R 31 ~R 33 Each independently represents a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms.

7. The solid electrolyte composition according to any one of claims 1 to 6, characterized in that The compound represented by the formula (1) is used as the component (B), and a compound represented by the following formula (X1) is also included: R X1 R X2 R X3 P(X1) In formula (X1), R X1 ~R X3 are independently a hydrogen atom or a substituent RA, R X1 ~R X3 At least one of them is a substituent RA.

8. The solid electrolyte composition according to any one of claims 1 to 7, characterized in that The ratio of the component (B) is 0.1 to 20% by mass based on the total of the component (A) and the component (B).

9. The solid electrolyte composition according to any one of claims 1 to 8, characterized in that The proportion of each of the components (B) exceeds 5% by volume based on the entire solid electrolyte composition.

10. The solid electrolyte composition according to any one of claims 1 to 9, characterized in that The ingredient (A) further contains halogen atoms.

11. The solid electrolyte composition according to any one of claims 1 to 10, characterized in that The component (A) contains one or more elements selected from the group consisting of chlorine (Cl), bromine (Br) and iodine (I).

12. The solid electrolyte composition according to any one of claims 1 to 11, characterized in that The component (A) contains chlorine (Cl).

13. The solid electrolyte composition according to any one of claims 1 to 12, characterized in that The component (A) includes chlorine (Cl) and bromine (Br).

14. The solid electrolyte composition according to any one of claims 1 to 13, characterized in that The component (A) has a crystalline structure.

15. The solid electrolyte composition according to any one of claims 1 to 14, characterized in that The component (A) has an argyrodite type crystal structure.

16. The solid electrolyte composition according to any one of claims 1 to 14, characterized in that The component (A) has a sulfide crystalline lithium superion conductor region type II crystal structure.

17. The solid electrolyte composition according to any one of claims 1 to 16, characterized in that (C) A solvent is included.

18. The solid electrolyte composition according to any one of claims 1 to 16, characterized in that The (C) solvent is not substantially contained.

19. The solid electrolyte composition according to any one of claims 1 to 18, characterized in that Contains (D) an electrode active material.

20. A solid electrolyte layer or electrode composite material, characterized in that: Obtained from the solid electrolyte composition according to any one of claims 1 to 19.

21. A lithium ion battery, characterized in that: Comprising the solid electrolyte layer or electrode composite material according to claim 20.

22. A lithium ion battery, wherein at least one of the electrode and the solid electrolyte layer comprises: (A) a sulfide solid electrolyte containing lithium, phosphorus and sulfur; and (B) one or more compounds selected from the compounds represented by the following formulae (1) to (3), R 11 R 12 R 13 PO(1) (NR 21 R 22 )(NR 23 R 24 )(NR 25 R 26 )PO(2) (R 31 O)(R 32 O)(R 33 O)PO(3) In formula (1), R 11 ~R 13 are independently a hydrogen atom or a substituent RA, R 11 ~R 13 At least one of them is a substituent RA, In formula (2), R 21 With R 22 , R 23 With R 24 and R 25 With R 26 At least one group of R in the formula (R) is bonded to each other to form a substituted or unsubstituted saturated or unsaturated ring, or is not bonded to each other. 21 ~R 26 are independently a hydrogen atom or a substituent RA, R 21 ~R 26 At least one of them is a substituent RA, In formula (3), R 31 ~R 33 are independently a hydrogen atom or a substituent RB, R 31 ~R 33 At least one of them is a substituent RB, The substituent RA is a substituted or unsubstituted alkyl group having 1 to 50 carbon atoms, a substituted or unsubstituted alkenyl group having 2 to 50 carbon atoms, a substituted or unsubstituted alkynyl group having 2 to 50 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 50 ring carbon atoms, a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms. The substituent RB is a substituted or unsubstituted aryl group having 6 to 50 ring carbon atoms, or a substituted or unsubstituted monovalent heterocyclic group having 5 to 50 ring atoms.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Solid electrolyte composition, molded body using the same, and all-solid secondary battery

    JP2020166994A